Direct hydrogenation of CO2 into valuable aromatics over K/Fe-Cu-Al @HZSM-5 tandem catalysts: Effects of zeolite surface acidity on aromatics formation - Zhang, Chundong; Hu, Kehao; Chen, Xixi; Xu, Lujing; Deng, Chao; Wang, Qiang; Gao, Ruxing; Jun, Ki Won; Kim, Seok Ki; Zhao, Tiansheng; Wan, Hui; Guan, Guofeng (Fuel Processing Technology, 2023)
Direct hydrogenation of carbon dioxide (CO2) to value-added aromatics can not only provide a sustainable aromatics synthesis route but also realize CO2 mitigation. However, it remains a great challenge to identify the optimal surface acidity and regulate the selective formation of aromatics during CO2 hydrogenation. Herein, we designed and prepared a series of K/Fe-Cu-Al@HZSM-5 tandem catalysts, and deeply investigated the effects of zeolite surface acidity on the catalytic performance, by changing the SiO2/Al2O3 ratios of HZSM-5 from 25 to 400. It was found that the surface acidity, especially for the Brønsted acidity, plays a crucial role in the aromatics formation. With an increasing Brønsted acidity from 0 to 290 μmol/g, the CO2 conversion keeps relatively stable (around 44%), however, the aromatics yield monotonously increases from 0.9 to 12.8%, indicating a distinct correlation with the Brønsted acidity. Among the obtained aromatics, the majority ones are C6–8 light aromatics, accounting for c.a. 30–60% within time on stream (TOS) of 24 h, but their proportion tends to gradually decrease with TOS, probably due to the catalyst deactivation by coking. Moreover, the possible reaction pathways for aromatics formation over the prepared K/Fe-Cu-Al@HZSM-5 tandem catalysts were also proposed.
Keywords: ACID properties; Catalyst effects; CO2 hydrogenation; HZSM-5 zeolites; Surface acidity; Tandem catalyst; Time on streams; Value-added aromatic; Zeolite surfaces; ]+ catalyst; Acid property; CO2 hydrogenation; HZSM-5 zeolite; Tandem catalyst; Value-added aromatics